Pope Francis, the Council, and the Medicine of Mercy - Vodola, Max (Studia canonica, 2017)
The pontificate of Pope Francis continues to attract international attention, often from non-Catholics and non-believers alike. His declaration of the Year of Mercy in 2015 on the fiftieth anniversary of the close of the Second Vatican Council has drawn attention to the style of his papacy that greatly resembles the much loved Pope John XXIII. Pope Francis is also the first pontiff not to have attended Vatican II. He does not enter the great theological debates regarding the interpretation of the Second Vatican Council that greatly preoccupied his predecessor Pope Benedict XVI. Pope Francis takes Vatican II as a theological given and appears to live the grace and spirit of the Council in his own distinctive way, especially his pastoral emphasis on servant leadership and a merciful Church at the peripheries.